Pengaruh Social Media Marketing terhadap Peningkatan Kinerja Bisnis UMKM Larisshop Grosir dalam Mencapai Pertumbuhan Penjualan dan Keunggulan Kompetitif - Sandra Dewi; Intan Muliana Rhamdhani (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the influence of social media marketing activities on the business performance of Larisshop MSMEs. A quantitative approach was employed using purposive sampling, involving 100 active resellers as respondents. The collected data were analyzed through multiple linear regression using SPSS software. The results indicate that the variables of social media marketing, consisting of context, communication, collaboration, and connection, simultaneously have a significant effect on business performance, as evidenced by the F-value of 47.053. Among these four variables, communication emerged as the most dominant factor influencing business performance, with a regression coefficient (β) of 0.393. This finding highlights that effective communication with customers—through product information, promotional activities, and daily interactions on social media platforms—plays a vital role in improving sales performance and sustaining business growth. Furthermore, the R-square value of 65% demonstrates that the independent variables examined in this study explained 65% of the variance in business performance, while the remaining 35% is influenced by other factors outside the model. This study emphasizes the importance of applying a social media marketing strategy based on the 4C concept (context, communication, collaboration, and connection) as a key effort to enhance MSME performance. The optimization of communication and connection should be prioritized by fostering intensive interactions, offering personalized services, and establishing long-term relationships with customers. By doing so, Larisshop MSMEs can strengthen customer loyalty while also expanding their market reach. In addition, this study provides recommendations for future research to explore other relevant variables, such as experiential marketing or consumer experience, as well as the utilization of emerging social media platforms to broaden the market. Such exploration is essential to offer a more comprehensive understanding of digital marketing strategies in supporting the growth and competitiveness of MSMEs in the digital transformation era.